Arbovirus surveillance using FTATM cards in modified CO2‐baited encephalitis virus surveillance traps in the Northern Territory, Australia. Issue 1 (23rd May 2019) - Kurucz, Nina; Minney‐Smith, Cara A; Johansen, Cheryl A
ABSTRACT: In 2016, modified CO2 ‐baited encephalitis virus surveillance (EVS) traps were evaluated for flavivirus surveillance in the Northern Territory, Australia. The traps were fitted with honey‐soaked nucleic acid preservation cards (FTA TM ) for mosquitoes to expectorate virus while feeding on the cards. Cards were tested for the presence of selected arboviruses, with two cards testing positive for Kunjin virus and Alfuy, while sentinel chickens tested in parallel also showed Kunjin virus activity at the same time. The results from the cards and vector mosquito feeding rates indicate that CO2 ‐baited EVS traps coupled with honey‐baited FTA TM cards are an effective tool for broad‐scale arbovirus surveillance.